REPRESENTASI POLITIK PEREMPUAN DALAM PARLEMEN DI INDIA PERIODE 1996 â 2009 - , CRISTIANY NURCAHAYA HARTATI SITOHANG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Thesis with the title "Political Representation of Women in Parliament in India Period 1996-2009" outlines of the development of women's political representation in parliament that India tend to be slow. Indian government's efforts to empower women one of which is to provide an opportunity to set a quota of 33% in general elections Lok Sabha (People's Assembly). The theme is interesting to discuss because even though India is known as the second largest democratic country after the United States, India still embrace the culture of patriarchy and caste systems are so entrenched in the community life. Or in other words, India is currently facing challenges in identifying and implementing strategies to balance the number of women and men in government and decision-making capacity. This study used qualitative data analysis techniques to accurately describe and interpret the meaning of a phenomenon that occurs in social life. While theoretical approaches is the theory of liberal feminism, political participation, and the quota system. The results of this study indicate that increased political representation of women in India are likely to be slow due to the independent variable, ie the achievement of objectives of the quota system and the strengthening of the party system that can lead to political marginalization.